Cause analysis manual incident investigation method & techniques - Forck, Fred (Rothstein Publishing, 2016)
A failure or accident brings your business to a sudden halt. How did it happen? What's at the root of the problem? What keeps it from happening again? Good detective work is needed -- but how do you go about it? In this new book, industry pioneer Fred Forck's seven-step cause analysis methodology guides you to the root of the incident, enabling you to act effectively to avoid loss of time, money, productivity, and quality.From 30+ years of experience as a performance improvement consultant, self-assessment team leader, and trainer, Fred Forck, CPT, understands what you need to get the job done. He leads you through a clear step-by-step process of root cause evaluation, quality improvement, and corrective action. Using these straightforward tools, you can avoid errors, increase reliability, enhance performance, and improve bottom-line results -- while creating a resilient culture that avoids repeat failures.